Creating value-added lemongrass oil from lemongrass for Tanjung Asri Women Farmers Group - Dewi Amrih; Mira Setiana; Bangkit Ina Ferawati; Ditha Kusuma Wardani; Tia Aulia Nashawa Himelda (Community Empowerment, 2024)
The Tanjung Asri Women Farmers Group (KWT) has great potential to develop businesses based on local resources, particularly lemongrass. Lemongrass, which offers numerous benefits, especially in the form of lemongrass oil, presents a promising business opportunity. However, the KWT members' lack of knowledge regarding lemongrass oil processing and business management poses a challenge. This community service activity aims to improve the knowledge and skills of KWT members in processing lemongrass into lemongrass oil and marketing the product through e-commerce. Through counseling, training, and demonstrations, KWT members were given an understanding of the benefits of lemongrass, lemongrass oil processing techniques, and online marketing strategies. The results of this activity indicate a significant increase in KWT members' knowledge about the added value of lemongrass and the business potential of lemongrass oil. In addition, KWT members also gained a better understanding of digital-based business management. Thus, this community service activity is expected to encourage the development of micro, small, and medium enterprises based on local resources in KWT Tanjung Asri.